A partial synthesis of 5, 8-O-dimethylshikonin and 6-isomer of 5, 8-O-dimethylshikonin. (1st November 2011) - Zheng, Xiaogang; Wang, Rubing; Zhu, Mengyuan; Jing, Zheng; Li, Shaoshun
A convenient synthesis of 5, 8-O-dimethylshikonin and the 6-isomer of 5, 8-O-dimethylshikonin was developed in 81.8% total yield from shikonin. (R)-4-Methyl-1-(1, 4, 5, 8-tetramethoxynaphthalen-2-yl)pent-3-en-1-ol was prepared in a one-pot two-step approach and then oxidised with ceric ammonium nitrate. This is simpler and the overall yield is higher than previous methods. The reaction conditions are milder and more environmentally friendly to environment, avoiding the use of the toxic and expensive reagents methyl iodide and chloromethyl ether and are more applicable to large-scale preparation. This is important because shikonin and its closely related derivatives have attracted much attention in view of their antitumor activities.